eCM 2021
DOI: 10.22203/ecm.v041a17
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of mesenchymal stem cell-derived extracellular vesicles in regenerative endodontics

Abstract: Regenerative endodontic procedures are an alternative to conventional root-canal treatment and apexification. There are two different tissue engineering approaches that are currently followed, both aiming at the colonisation of the cleaned pulp space by pluripotent cells and subsequent pulp regeneration. Firstly, the transplantation of mesenchymal stem cells (MSCs), and secondly a cell-free strategy that relies on bioactive molecules to trigger the recruitment of the patient’s own cells. The first approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“… 2–4 Moreover, the clinical application of stem cells also faces restrictions on acquisition, expansion, transportation, and storage. 5 , 6 Therefore, the exploration of new therapies to promote dental pulp regeneration using cell-homing techniques has become an urgent need.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2–4 Moreover, the clinical application of stem cells also faces restrictions on acquisition, expansion, transportation, and storage. 5 , 6 Therefore, the exploration of new therapies to promote dental pulp regeneration using cell-homing techniques has become an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are a type of extracellular vesicles and can be used in therapeutic applications due to their important roles in intercellular communication. 5 , 6 Exosomes have also been used in oral regenerative medicine, specifically, for pulp regeneration, and the effectiveness of the technique has been proven. Huang et al found that exosomes secreted by osteoblast-induced dental pulp stem cells (DPSCs) could effectively induce DPSC differentiation in vitro, and could regenerate pulp-like tissue with high expression of odontogenic proteins in nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…To conclude, although when applied, the CB show promising effects (recent studies claim post-treatment formation of a vascularized tissue with a normal physiological response-vital pulp-like tissue), they are relatively complex, expensive, and not yet thoroughly explored [129]. There are also no clear ideal strategies, or AAE/EAO recommended protocols [4,5].…”
Section: Ret Strategiesmentioning
confidence: 99%
“…Following the harvest, exosomes can even be stored or biobanked through the process of dry-freezing, making them more available and more practical for scientific or clinical use [142]. A recent review paper by Ivica et al focuses on possible exosomes applications in dentistry [5]. The authors state that the evidence for exosome use in regenerative dentistry comes from limited in vitro or animal in vivo studies, so there are currently no sufficient data for safe and practical clinical usage.…”
Section: Exosome Strategymentioning
confidence: 99%
See 1 more Smart Citation